Penerapan Model Pembelajaran Diskursus Multy Reprecentacy (DMR) untuk Meningkatkan Pemahaman dan Prestasi Belajar Siswa - Muhammad Aidil Nur ; Fauzan Azmi (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
The research problem is the low activity in the classroom in the learning process, especially in the process of activity and achievement which is still rigid. The purpose of this study was to find out by applying the Discourse Multy Representace learning model that could improve student activity and achievement abilities. This research was conducted at SMP N 1 Hinai in the 2020/2021 academic year. With the subject of 36 students. This research was formed in the CAR research. In data collection, the data obtained are student learning activity observation sheets and student learning outcomes tests. For data analysis used quantitative and qualitative data. Based on data analysis, the result of student activity (cycle I was 38.88%), while in cycle II it was (86.21%). On student learning outcomes from the pretest data obtained a score of 62.7 with 12 students who completed and 24 students who did not complete. In the first cycle posttest obtained a value of (73.19%) with a total of 8 students who completed from 28 students who did not complete. And in the second cycle posttest with a value of (94.16) with 35 students who completed and 1 student who did not complete. This shows the success of the research conducted. It can be concluded that the application of collaborating the Discourse Multi-Representation learning model with the concept sentence on the students has succeeded with what was expected. Keywords: Multi-Representation Discourse; improve; Understanding and learning achievement; Students